Engineering 3D printed bioactive composite scaffolds based on the combination of aliphatic polyester and calcium phosphates for bone tissue regeneration - Backes, Eduardo H. (2021)
In this study, polylactic acid (PLA) filled with hydroxyapatite (HA) or beta-tricalcium phosphate (TCP) in 5 wt% and 10 wt% of concentration were produced employing twin-screw extrusion followed by fused filament fabrication in two different architectures, varying the orientation of fibers of adjacent layers. The extruded 3D filaments presented suitable rheological and thermal properties to manufacture of 3D scaffolds envisaging bone tissue engineering. The produced scaffolds exhibited a high level of printing accuracy related to the 3D model; confirmed by micro-CT and electron microscopy analysis. The developed architectures presented mechanical properties compatible with human bone replacement. The addition of HA and TCP made the filaments bioactive, and the deposition of new calcium phosphates was observed upon 7 days of incubation in simulated body fluid, exemplifying a microenvironment suitable for cell attachment and proliferation. After 7 days of cell culture, the constructs with a higher percentage of HA and TCP demonstrated a significantly superior amount of DNA when compared to neat PLA, indicating that higher concentrations of HA and TCP could guide a good cellular response and increasing cell cytocompatibility. Differentiation tests were performed, and the biocomposites of PLA/HA and PLA/TCP exhibited earlier markers of cell differentiation as confirmed by alkaline phosphatase and alizarin red assays. The 3D printed composite scaffolds, manufactured with bioactive materials and adequate porous size, supported cell attachment, proliferation, and differentiation ,which together with their scalability, promise a high potential for bone tissue engineering applications.